PEMODELAN REGRESI LOGISTIK BINER TERHADAP PENERIMAAN PEGAWAI DI PT XYZ JAKARTA - Ali Ilham Sofiyat; Awaluddin Tjalla; Mahdiyah Mahdiyah (Fakultas Sains Dan Teknologi, 2023)
Recruitment is a selection pattern implemented by PT XYZ to accept employees placed in various company branches, through a written exam. From the many applicants, there were some who were accepted and the rest were not accepted. Therefore, we want to know the characteristics and modeling using the binary logistic regression method with the response variable is the status of acceptance which has a value of one is accepted and a value of zero if it fails to be accepted. Based on the results of the analysis it is known that the number of applicants who were declared accepted was 50% of the participants, while the remaining 50% of the applicants were declared not accepted. In binary logistic regression modeling, the influential variables are education (last length of education) and experience (work experience).